Inflammation Markers in Patients with Bipolar Disorder Who Have Committed Offenses and Their Relationship with Criminal Behavior - Sirlier Emir, Burcu; Yildiz, Sevler; Kazgan Kilicaslan, Asli; Kurt, Osman; Ugur, Kerim; Tabara, Muhammed Fatih; Aydin, Sueleyman (Mdpi, 2023)
Background and Objectives: This study aimed to examine the function of various inflammation parameters and their interactions in the pathology of Bipolar disorder (BD) and to assess whether they could be biomarkers in the relationship between criminal behavior and BD. Materials and Methods: Overall, 1029 participants, including 343 patients with BD who have committed offenses, 343 nonoffending patients with BD, and 343 healthy controls, were included in this retrospective study. Neutrophil, lymphocyte, monocyte, and platelet counts; high-density lipoprotein (HDL-c) levels; systemic immune-inflammatory index (SII), systemic inflammatory response index (SIRI), neutrophil to high-density lipoprotein ratio (NHR), lymphocyte to high-density lipoprotein ratio (LHR), monocyte to high-density lipoprotein ratio (MHR), platelet to high-density lipoprotein ratio (PHR) were measured. Results: Significant differences were observed between the groups in terms of SII, SIRI, NHR, LHR, MHR, PHR, neutrophil, and monocyte values (p < 0.001). The lymphocyte counts were significantly higher in the patients with BD who committed offenses (p = 0.04). The platelet counts were significantly lower in the patients with BD who committed offenses compared to nonoffending patients with BD (p = 0.015). The HDL-c levels were significantly lower in the patients with BD who have committed offenses than those of nonoffending patients with BD (p < 0.001). Bipolar disorder, not receiving active psychiatric treatment, having a diagnosis of bipolar manic episodes, and having low platelet and HDL values constitute a risk of involvement in crime. Conclusions: The present study emphasizes the role of systemic inflammation in the pathophysiology of patients with BD with and without criminal offenses and the relationship between inflammation and criminal behavior.
Keywords: bipolar disorder; inflammation; systemic inflammatory response index; systemic immune inflammatory index; high-density lipoprotein; criminal behavior